Benzoquinone induces ROS-dependent mitochondria-mediated apoptosis in HL-60 cells. (April 2018) - Sun, Shuqiang; Zhang, Chunxiao; Gao, Jiahao; Qin, Qiongyu; Zhang, Yaya; Zhu, Hua; Yang, Xinjun; Yang, Dongren; Yan, Hongtao
Benzene exposure affects the hematopoietic system and leads to the occurrence of various types of leukemia and hematotoxicity. It has been confirmed that active metabolites of benzene, including 1, 4-benzoquinone (1, 4-BQ), can induce reactive oxygen species (ROS) and apoptosis in the bone marrow, and recent studies have also suggested that benzene exposure can affect mitochondrial function in both experimental animals and cell lines. However, the potential relationship among ROS production, mitochondrial damages, and subsequent apoptosis following benzene exposure has not been well studied in detail. In the present study, we utilized HL-60 cells, a well-characterized human myeloid cell line, as an in vitro model and examined the effects of 1, 4-BQ on intracellular ROS formation, mitochondria damage, and the occurrence of apoptotic events with or without using the ROS scavenger N -acetyl-l -cysteine (NAC). The results demonstrated that 1, 4-BQ could dose-dependently induce production of ROS and mitochondrial damage as characterized by mitochondrial membrane potential disruption, mitochondrial ultrastructure alteration, and induced apoptosis and activated caspase-3 and caspase-9. Preincubation of HL-60 cells with NAC prior to 1, 4-BQ treatment could block 1, 4-BQ-induced production of ROS and the occurrence of apoptosis. These results demonstrated that 1, 4-BQ induced apoptosis in HL-60 cells through a ROS-dependent mitochondrial-mediated pathway.